PENGARUH KECERDASAN MATEMATIS LOGIS DAN KEPERCAYAAN DIRI MELALUI KEMAMPUAN KEMANDIRIAN BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI DI KABUPATEN SINJAI: The Influence of Logical Mathematics Intelligence and Self Confident through Logical Independent Learning toward Mathematics Learning Achievement of grade VIII Students at Public Junior High Schools in Sinjai District - Harjuna, Hariani; Tiro, M. Arif; -, Alimuddin (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2016)
This research was aimed to: (1) discover the descriptive of logical mathematics intelligence, independent learning, self confident, mathematics learning achievement of class VIII students at SMPN (Public Junior High School) in Sinjai district, (2) discover the extend of direct and indirect enfluence of logical mathematics intelligence through independent learning toward mathematics learning achievement of the class VIII students at SMPN in Sinjai district, (3) discover the extend of direct and indirect influence of self confident through independent learning toward mathematics learning achievement of class VIII at SMPN in Sinjai district.This research was a causality ex-post-facto research. The population of this research was the students of SMPN in Sinjai district. The data was collected through 216 samples who were chosen by using proportional stratified random sampling technique. The data was analyzed by descriptive statistics and path analysis.The result of this research showed that: (1) mostly the students of class VIII at SMPN in Sinjai district had; logical mathematics intelligence in low category, high self confident in learning mathematics in high category, independent study in mathematics in moderate category, and mathematics learning achievement in low category; (2) logical mathematics intelligence gave positive influence toward mathematics learning achievement wheather directly or indirectly (through independent learning). The amount of logical mathematics intelligence towards the students learning achievement in mathematics was 60% and the amount of logical mathematics intelligence towards the students learning achievement through attitude in learning mathematics was 3% and the amount of logical mathematics intelligence towards the students achievement in mathematics was 63%. Self confident gave positive influence toward mathematics learning achievement wheather directly or indirectly (through independent learning). The amount of self confidence towards the students learning achievement in mathematics was 6% and the amount of self confidence towards the students learning achievement through attitude in learning mathematics was 8% and the amount of self confidence towards the students achievement in mathematics was 14%.